(Poly)phenol characterisation in white and red cardoon stalks: could the sous-vide technique improve their bioaccessibility?. (17th February 2022) - Huarte, Estíbaliz; Trius-Soler, Marta; Domínguez-Fernández, Maite; De Peña, María-Paz; Cid, Concepción
Abstract: This study aims to evaluate whether sous-vide cooking better preserves the (poly)phenol content and profile of red and white cardoon stalks versus traditional boiling, both before and after simulated oral-gastro-intestinal digestion. Thirty one (poly)phenols were quantified in red and white cardoon by HPLC-MS/MS, phenolic acids being >95%, and 5–caffeoylquinic and 1, 5–dicaffeoylquinic acids the major ones. Although both varieties showed a similar profile, raw red cardoon had 1.7-fold higher (poly)phenol content than raw white cardoon. Culinary treatments decreased (poly)phenol content, but sous-vide cooked cardoon had a greater content than the boiled one, suggesting a protective effect. After gastrointestinal digestion, (poly)phenol bioaccessibility of boiled and sous-vide cooked cardoon (52.6–90.5%) was higher than that of raw samples (0.2–0.7%), although sous-vide system no longer played a protective effect compared to boiling. In summary, red cardoon was a richer source of bioaccessible (poly)phenols than white cardoon, even sous-vide cooked or boiled.